Hubungan Kompetensi Sosial Guru Pendidikan Agama Islam terhadap Pembentukan Karakter Siswa Kelas VIII MTs Miftahul Jannah Pantai Cermin Kecamatan Tanjung Pura - Umi Aisyah; Nurmisdaramayani Nurmisdaramayani ; Fauzan Azmi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
This research is concerned with the relationship of the social competence of Islamic religious education teachers to the formation of students' character. The purpose of this study was to determine the relationship of social competence of Islamic religious education teachers to the character formation of eighth grade students of Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin. This research is a quantitative research research. The implementation of this research was carried out in 2021 in April to June 2021. The purpose of this study was to determine the relationship of the social competence of Islamic religious education teachers to the character building of the eighth grade students of Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin. the two variables have a significant relationship. To prove this, the author conducted a study on the title. This research was conducted on 69 students of class VIII Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin which were used as research samples. Data collection tools are library research, observation, questionnaires and interviews. The results of the questionnaire were processed by tabulating the data to determine the frequency. Based on the discussion of the research results in this thesis, it can be seen that the social competence of Islamic religious education teachers for class VIII Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin is very good (59%). While the character formation of grade VIII Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin students in general is very good (54%). The results of the tabulation calculation between the relationship of the social competence of Islamic religious education teachers to the character formation of the eighth grade students of Madrasah Tsanawiyah Miftahul Jannah Pantai Cermin with a moderate or sufficient level of significance.